Minimal invasiveness in nonsurgical periodontal therapy - Ribeiro, Fernanda V.; Mehta, Jaimini J.; Monteiro, Mabelle F.; Moore, Jatinder; Casati, Marcio Z.; Nibali, Luigi (Periodontology 2000, 2023)
Periodontal treatment is quickly moving towards a philosophy consisting of a less invasive approach. In this context, minimally invasive nonsurgical therapy (MINST) is a promising option. This paper reviews the concepts behind minimal invasiveness in nonsurgical periodontology and reports the state‐of the art evidence for this topic. Instruments used and protocols suggested for these applications are introduced and discussed. The original papers reviewed show probing pocket depth (PPD) reductions and clinical attachment level (CAL) gains ranging from 2 to 4 mm between baseline and 6 months to 5 years posttreatment for intrabony defects and from 1.5 to 3 mm between baseline and 2‐6 months of follow‐up for full‐mouth results. These clinical outcomes are accompanied by statistically significant reductions in radiographic bone defect depth and increases in intrabony defect angles posttreatment. Wound healing mechanisms following MINST are presented, and clinical applications and directions for future research are suggested.